Non-noble metal oxygen reduction electrocatalyst based on strong chelation as well as preparation method and application of non-noble metal oxygen reduction electrocatalyst
Through the strong chelation effect of iron ions and organic complexes, a non-precious metal oxygen reduction electrocatalyst with a high degree of graphitization was prepared, which solved the problem of defects in the M-N-C catalysts and low degree of graphitization of carbon support during the pyrolysis process, achieved high activity and long-term stability of the catalyst, and provided a new path to replace platinum-based catalysts.
Patent Information
- Application Number
- CN202510060469.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In the prior art, transition metal atom-nitrogen-carbon (M-N-C) catalysts are prone to defects during the pyrolysis process, resulting in insufficient ORR activity and stability, and low degree of graphitization of the carbon support, which is prone to oxidation and corrosion, affecting the long-term stability of the catalyst.
Through strong chelation between iron ions (Fe3+) and functional groups such as -COOH and -NH2 in the organic complex, a non-precious metal oxygen reduction electrocatalyst with a high degree of graphitization is prepared, and a highly directed and stable coordination structure is used to form a carboxyl group and metal ions, limit the movement of carbon atoms and promote the formation of graphite structure.
The high graphitization and high stability of the catalyst are achieved, the dissolution of metal ions during the acidic ORR process is reduced, the activity and long-term operating performance of M-N-C catalysts are improved, and a new path to replace traditional platinum-based catalysts is provided.
Smart Images

Figure CN119890334A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy technology, and in particular to a non-precious metal oxygen reduction electrocatalyst based on strong chelation, and a preparation method and application thereof. Background Art
[0002] As a hydrogen energy conversion device, proton exchange membrane fuel cell (PEMFC) has the advantages of high conversion efficiency, high power density and environmental protection, and is considered to be one of the important ways to achieve the transition to clean energy. However, the cathode oxygen reduction reaction (ORR) rate of PEMFC is slow. The expensive platinum-based catalyst has become an efficient ORR catalyst, but its high cost and easy poisoning seriously hinder the commercial development of PEMFC. Therefore, the development of low-cost, highly active and highly stable non-precious metal catalysts to replace Pt-based catalysts has become an important measure to promote the development of PEMFC.
[0003] Transition metal atom-nitrogen-carbon (MNC) catalysts have become the most promising alternatives to platinum-based catalysts. Most of them are prepared by pyrolysis of transition metal-loaded metal organic frameworks (MOFs). This type of synthesis method has certain limitations. First, during the pyrolysis process, the metal center ions of MOFs will sublimate to produce defects, thereby inducing Fe 3+ The filling makes the bonding between transition metal atoms and nitrogen atoms weaker and the degree of graphitization lower, resulting in the dissolution of a large amount of metal in the acidic ORR process, which greatly limits the intrinsic activity and stability of ORR; secondly, the low degree of graphitization of the catalyst carbon support prepared by this synthesis method will cause it to undergo oxidative corrosion during long-term operation, leading to the detachment of active sites of the entire catalyst layer and even the collapse of the structure. Summary of the invention
[0004] In view of this, the present application provides a non-precious metal oxygen reduction electrocatalyst based on strong chelation, a preparation method and application thereof, using iron ions (Fe 3+ ) and organic complexes (such as 2-aminoterephthalic acid (H2atpt), nicotinamide (VPP), acetylsalicylic acid (Aspirin), etc.) with -COOH, -NH2 and other functional groups and a high degree of order to prepare a high degree of graphitization high stability non-precious metal oxygen reduction electrocatalyst; the entire synthesis process is simple to operate, and no hazardous solvents are used. A single batch production can reach more than gram level, achieving high atomic utilization while maintaining high stability. It can provide a new idea for preparing high activity and high stability fuel cell cathode oxygen reduction non-precious metal catalysts and realizing commercial large-scale production, which can effectively overcome the defects of the above-mentioned existing technologies.
[0005] The first aspect of the present application provides a method for preparing a non-noble metal oxygen reduction electrocatalyst based on strong chelation, comprising the following steps:
[0006] S1. Add the organic complex into ultrapure water, heat and stir until completely dissolved, then add the salt template and the iron source in sequence, and heat and stir until a dark yellow gel suspension is obtained;
[0007] S2, adding an ammonium source to the gel suspension, continuing to stir until completely dissolved, heating to evaporate part of the solvent, stopping heating, and freeze-drying to obtain an orange powder;
[0008] S3, then pyrolyzing the orange powder to obtain a black powder;
[0009] S4, washing the black powder with acid, filtering and drying to obtain a precursor product;
[0010] S5. The precursor product is pyrolyzed again to obtain an NH4Cl-organic complex-Fe catalyst, i.e., a non-precious metal oxygen reduction electrocatalyst based on strong chelation.
[0011] Specifically, the steps include:
[0012] S1. Add the organic complex into ultrapure water, heat and stir until completely dissolved, then add potassium chloride and anhydrous ferric chloride, and heat and stir until a dark yellow gel suspension is obtained;
[0013] S2, adding ammonium chloride to the gel suspension, continuing to stir until completely dissolved, heating to evaporate part of the solvent, stopping heating, and freeze-drying to obtain an orange powder;
[0014] S3, then pyrolyzing the orange powder to obtain a black powder;
[0015] S4, washing the black powder with acid, filtering and drying to obtain a precursor product:
[0016] S5. The precursor product is pyrolyzed again to obtain an NH4Cl-organic complex-Fe catalyst, i.e., a non-precious metal oxygen reduction electrocatalyst based on strong chelation.
[0017] The present application utilizes the advantages of strong chelation of metal ions, extremely high coordination order and avoiding the generation of a large number of defects in the functional groups (such as -COOH, -NH2, etc.) in nitrogen-containing carboxylic acid organic complexes to prepare MNC catalysts, which can achieve high graphitization of the catalyst without losing high activity, thereby solving the above problems. The advantages of this preparation method are as follows: First, the oxygen atom (O) in the carboxyl group can be used as a coordinating atom to construct a monodentate coordination with the metal ion. In certain circumstances, the oxygen atom can also be connected to two different metal sites to form a bidentate coordination. This coordination mode has a high degree of directionality and extremely strong stability. It can avoid defects caused by the sublimation of the metal center ion in the MOF while restricting the movement of carbon atoms, promoting a more orderly rearrangement of carbon atoms, and finally forming a regular graphite structure; second, the carboxyl group can also construct a bridging structure with the carboxyl group in other acids, thereby further improving the chelation stability of the metal ion; third, the carboxyl group and the amino group can participate in the coordination reaction together, combining with the metal ion by means of the O, N-chelation mode, and can also form a more complex structure by means of the bridging effect, such as a tridentate coordination configuration. In this way, the preparation method can not only greatly improve the utilization rate of metal atoms and greatly enhance the binding energy of MN bonds in MNC catalysts, but also achieve high graphitization, effectively reduce the amount of metal ion dissolution during the acidic ORR process, and achieve high stability of the catalyst. Therefore, the preparation of highly graphitized fuel cell cathode ORR non-precious metal catalysts through the strong chelation between metal ions and nitrogen-containing carboxylic acid organic complexes is a new path to replace the traditional method of preparing MNC catalysts.
[0018] Preferably, in step S1, the organic complex is selected from one of 2-aminoterephthalic acid, nicotinamide, and acetylsalicylic acid; or
[0019] In step S1, the salt template is selected from one of potassium chloride, zinc chloride and sodium chloride; or
[0020] In step S1, the iron source is selected from one of anhydrous ferric chloride, ferric sulfate, and ferric nitrate; or
[0021] In step S2, the ammonium source is selected from one of ammonium chloride, ammonium sulfate and ammonium nitrate.
[0022] Preferably, in step S3, the specific conditions of the pyrolysis are: first pyrolyze at 500°C for 1 hour, then heat to 1000°C, and pyrolyze at this temperature for 1 hour; or
[0023] In step S5, the pyrolysis temperature is 1000° C. and the pyrolysis time is 1 hour.
[0024] Preferably, in step S4, the specific conditions for pickling are: pickling in H2SO4 solution for 10-15 hours.
[0025] Preferably, the usage ratio of the organic complex, ultrapure water, potassium chloride, anhydrous ferric chloride and ammonium chloride is (1-9 g):200 mL:(1-5 g):(0.1-1 g):(1-8 g).
[0026] The second aspect of the present application also provides a non-precious metal oxygen reduction electrocatalyst based on strong chelation, which is a non-precious metal oxygen reduction electrocatalyst based on strong chelation prepared by the above method.
[0027] The third aspect of the present application also provides the use of the above-mentioned non-precious metal oxygen reduction electrocatalyst based on strong chelation in battery cathode materials.
[0028] The fourth aspect of the present application also provides a working electrode, which includes the above-mentioned non-precious metal oxygen reduction electrocatalyst based on strong chelation.
[0029] The fifth aspect of the present application also provides a method for preparing the above-mentioned working electrode, comprising the following steps:
[0030] 10 mg of the non-precious metal oxygen reduction electrocatalyst material based on strong chelation was weighed, and 1 mL of isopropanol was added successively and ultrasonicated until uniform, and then dropped onto the disk electrode to obtain a working electrode. Finally, the oxygen reduction electrochemical performance test was performed.
[0031] Compared with the prior art, this application has the following beneficial effects:
[0032] This application utilizes iron ions (Fe 3+ ) and organic complexes (such as 2-aminoterephthalic acid (H2atpt), nicotinamide (VPP), acetylsalicylic acid (Aspirin), etc.) The strong chelation and high order between the -COOH, -NH2 and other functional groups are used to prepare non-precious metal oxygen reduction electrocatalysts with a high degree of graphitization; the entire synthesis process is simple to operate and no hazardous solvents are used. A single batch production can reach more than gram level, achieving high atomic utilization while maintaining high stability. It can provide a new idea for the preparation of highly active and highly stable non-precious metal catalysts for fuel cell cathode oxygen reduction and realizing commercial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1This is a SEM image of the NH4Cl-H2atpt-Fe catalyst of Example 1 of the present application;
[0035] Figure 2 This is a SEM image of the NH4Cl-VPP-Fe catalyst of Example 2 of the present application;
[0036] Figure 3 The Raman comparison diagram of the NH4Cl-H2atpt-Fe catalyst, NH4Cl-VPP-Fe catalyst and NH4Cl-Aspirin-Fe catalyst of Examples 1-3 of the present application (I D Indicates the degree of defect, I G Indicates the degree of graphitization);
[0037] Figure 4 This is a SCV comparison chart of the NH4Cl-H2atpt-Fe catalyst, NH4Cl-VPP-Fe catalyst and NH4Cl-Aspirin-Fe catalyst of Examples 1-3 of the present application. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0039] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0040] In the following examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0041] Example 1
[0042] 3g of H2atpt was added to 200ml of ultrapure water and heated and stirred until completely dissolved. Subsequently, 3g of potassium chloride and 0.55g of anhydrous ferric chloride were added to the above solution in sequence, and heated and stirred until a dark yellow gel suspension was obtained. 5g of ammonium chloride was added and continued to be stirred until completely dissolved. When the solvent was heated to evaporate to 50mL, the heating was stopped and the sample was dried in a freeze dryer to obtain an orange powder. The sample was then placed in a tube furnace for pyrolysis, first at 500°C for 1h, and then heated to 1000°C for 1h to obtain a black powder. The black powder was acid-washed in a H2SO4 solution for 12h. After filtration and drying, a secondary pyrolysis was performed at a pyrolysis temperature of 1000°C and a pyrolysis time of 1h to obtain an NH4Cl-H2atpt-Fe catalyst, which was used for subsequent characterization and electrochemical testing.
[0043] Example 2
[0044] 5g of VPP was added to 200ml of ultrapure water and heated and stirred until completely dissolved. Then 5g of potassium chloride and 0.55g of anhydrous ferric chloride were added to the above solution in sequence, and heated and stirred until a dark yellow gel suspension was obtained. 5g of ammonium chloride was added and continued to be stirred until completely dissolved. When the solvent was heated to evaporate to 50mL, the heating was stopped and the sample was dried in a freeze dryer to obtain an orange powder. The sample was then placed in a tube furnace for pyrolysis, first at 500℃ for 1h, and then heated to 1000℃ for 1h to obtain a black powder. The black powder was acid-washed in a H2SO4 solution for 12h. After filtration and drying, a secondary pyrolysis was carried out at a pyrolysis temperature of 1000℃ and a pyrolysis time of 1h to obtain an NH4Cl-VPP-Fe catalyst, which was used for subsequent characterization and electrochemical testing.
[0045] Example 3
[0046] 4g of Aspirin was added to 200ml of ultrapure water and heated and stirred until completely dissolved. Then 4g of potassium chloride and 0.55g of anhydrous ferric chloride were added to the above solution in sequence, and heated and stirred until a dark yellow gel suspension was obtained. 5g of ammonium chloride was added and continued to be stirred until completely dissolved. When the solvent was heated to evaporate to 50mL, the heating was stopped and the sample was placed in a freeze dryer for drying to obtain an orange powder. The sample was then placed in a tube furnace for pyrolysis, first at 500℃ for 1h, and then heated to 1000℃ for 1h to obtain a black powder. The black powder was acid-washed in H2SO4 solution for 12h. After filtration and drying, it was subjected to secondary pyrolysis at a pyrolysis temperature of 1000℃ and a pyrolysis time of 1h to obtain the NH4Cl-Aspirin-Fe catalyst, which was used for subsequent characterization and electrochemical testing.
[0047] Comparative Example 1
[0048] 3g of XC-72 carbon powder was added to 200ml of ultrapure water and heated and stirred until completely dissolved. Subsequently, 3g of potassium chloride and 0.55g of anhydrous ferric chloride were added to the above solution in sequence, and heated and stirred until a dark yellow gel suspension was obtained. 5g of ammonium chloride was added and continued to be stirred until completely dissolved. When the solvent was heated to evaporate to 50mL, the heating was stopped and the sample was dried in a freeze dryer to obtain an orange powder. The sample was then placed in a tube furnace for pyrolysis, first at 500℃ for 1h, and then heated to 1000℃ for 1h to obtain a black powder. The black powder was acid-washed in a H2SO4 solution for 12h. After filtration and drying, a secondary pyrolysis was performed at a pyrolysis temperature of 1000℃ and a pyrolysis time of 1h to obtain an NH4Cl-XC-Fe catalyst, which was used for subsequent characterization and electrochemical testing.
[0049] The experimental scheme provided in this comparative example can refer to Example 1, except that XC-72 carbon powder without chelating effect is used instead of 2-aminoterephthalic acid (H2atpt).
[0050] Test Case
[0051] 10 mg of each non-precious metal oxygen reduction electrocatalyst material based on strong chelation in Examples 1-3 was weighed, and 1 mL of isopropanol was added successively and ultrasonicated until uniform. After uniformity, the mixture was dropped onto a disk electrode for oxygen reduction electrochemical performance testing.
[0052] Figure 1 In the experiment, the prepared NH4Cl-H2atpt-Fe catalyst was in strip shape and no obvious iron nanoparticles were observed.
[0053] Figure 2 In the experiment, the prepared NH4Cl-VPP-Fe catalyst was in flaky form and no obvious iron nanoparticles were observed.
[0054] Figure 3 In the comparison of Raman test results, it can be seen that the graphitization degree of non-precious metal oxygen reduction electrocatalysts based on strong chelation prepared by different organic complexes is different. D Indicates the degree of defect, I G Indicates the degree of graphitization, I D / I G The larger the value, the higher the degree of defects, and vice versa, the higher the degree of graphitization. By comparison, it can be seen that the prepared NH4Cl-H2atpt-Fe catalyst has the highest degree of graphitization, followed by the NH4Cl-VPP-Fe catalyst, and finally the NH4Cl-Aspirin-Fe catalyst.
[0055] Figure 4The oxygen reduction performance of the three catalysts was tested. The test results showed that the NH4Cl-H2atpt-Fe catalyst had the best oxygen reduction performance. In the acid electrolyte test, the half-wave potential (E 1 / 2 ) can reach 0.82V, followed by NH4Cl-Aspirin-Fe catalyst, E 1 / 2 is 0.80V, and finally the NH4Cl-VPP-Fe catalyst, E 1 / 2 is 0.78V.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a non-noble metal oxygen reduction electrocatalyst based on strong chelation, characterized in that: The following steps are involved: S1. Add the organic complex into ultrapure water, heat and stir until completely dissolved, then add the salt template and the iron source in sequence, and heat and stir until a dark yellow gel suspension is obtained; S2, adding an ammonium source to the gel suspension, continuing to stir until completely dissolved, heating to evaporate part of the solvent, stopping heating, and freeze-drying to obtain an orange powder; S3, then pyrolyzing the orange powder to obtain a black powder; S4, washing the black powder with acid, filtering and drying to obtain a precursor product; S5. The precursor product is pyrolyzed again to obtain an NH4Cl-organic complex-Fe catalyst, i.e., a non-precious metal oxygen reduction electrocatalyst based on strong chelation.
2. The method for preparing a non-noble metal oxygen reduction electrocatalyst based on strong chelation according to claim 1, characterized in that: In step S1, the organic complex is selected from one of 2-aminoterephthalic acid, nicotinamide, and acetylsalicylic acid; or In step S1, the salt template is selected from one of potassium chloride, zinc chloride and sodium chloride; or In step S1, the iron source is selected from one of anhydrous ferric chloride, ferric sulfate, and ferric nitrate; or In step S2, the ammonium source is selected from one of ammonium chloride, ammonium sulfate and ammonium nitrate.
3. The method for preparing a non-noble metal oxygen reduction electrocatalyst based on strong chelation according to claim 1, characterized in that: In step S3, the specific conditions of the pyrolysis are: first pyrolyze at 500°C for 1 hour, then heat to 1000°C, and pyrolyze at this temperature for 1 hour; or In step S5, the pyrolysis temperature is 1000° C. and the pyrolysis time is 1 hour.
4. The method for preparing a non-noble metal oxygen reduction electrocatalyst based on strong chelation according to claim 1, characterized in that: In step S4, the specific conditions for pickling are: pickling in H2SO4 solution for 10-15 hours.
5. The method for preparing a non-noble metal oxygen reduction electrocatalyst based on strong chelation according to claim 2, characterized in that: The usage ratio of the organic complex, ultrapure water, potassium chloride, anhydrous ferric chloride and ammonium chloride is (1-9 g):200 mL:(1-5 g):(0.1-1 g):(1-8 g).
6. A non-precious metal oxygen reduction electrocatalyst based on strong chelation, characterized in that: A non-noble metal oxygen reduction electrocatalyst based on strong chelation prepared by the method described in any one of claims 1 to 5.
7. Use of the non-precious metal oxygen reduction electrocatalyst based on strong chelation as claimed in claim 6 in battery cathode materials.
8. A working electrode, characterized in that It includes the non-noble metal oxygen reduction electrocatalyst based on strong chelation as described in claim 6.
9. A method for preparing the working electrode according to claim 8, characterized in that: The following steps are involved: 10 mg of the non-precious metal oxygen reduction electrocatalyst material based on strong chelation was weighed, and 1 mL of isopropanol was added successively and ultrasonicated until uniform, and then the mixture was dropped onto the disk electrode to obtain a working electrode.
Citation Information
Patent Citations
Method for solid-phase macrosynthesis of non-noble metal oxygen reduction catalyst, and catalyst and application thereof
CN110474059A
Preparation method of non-noble metal oxygen reduction catalyst
CN114678542A
Transition metal monatomic catalyst for cathode oxygen reduction reaction and preparation method of transition metal monatomic catalyst
CN116190682A
High performance, high durability non-precious metal fuel cell catalysts
US20110319257A1